Revolutionizing Identity Verification: AI-Driven Digital Identity Solutions for a Secure and Seamless Future - Venkata Krishna Ramesh Kumar Koppireddy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article explores the revolutionary potential of AI-driven digital identity solutions in reshaping identity verification and management. It examines the core technologies underpinning these systems, including biometric authentication, behavioral analytics, and advanced encryption methods. The article discusses the wide-ranging applications of digital identity across sectors such as travel, finance, healthcare, and government services, highlighting the benefits of enhanced security, improved user convenience, and increased efficiency. Key challenges are addressed, including data protection concerns, technological infrastructure requirements, and the need for inclusive accessibility. The article also considers future directions, such as advancements in AI and biometrics, integration with emerging technologies like blockchain, and efforts towards global standardization. By providing a comprehensive overview of the current state and future prospects of AI-driven digital identity solutions, this paper underscores their transformative impact on security, privacy, and user experience in the digital age, while emphasizing the importance of balancing innovation with ethical considerations.
Keywords: AI-driven digital identity; Biometric authentication; Behavioral analytics; Multi-factor authentication; Cross-border identity verification